In vitro and in vivo evaluation of 2-chloroethylnitrosourea derivatives as antitumor agents - Sen, A.; Goswami, K.K.; Mallick, A.; Saxena, A.K.; Sanyal, U.; Baral, R. (Experimental Oncology, 2015)
Aim: To evaluate potential of Naphthal-NU, Napro-NU and 5-Nitro-naphthal-NU, 2-chloroethylnitrosourea compounds with substituted naphthalimide in the pre-clinical studies. Materials and Methods: In vitro cytotoxicity of three nitrosoureas was determined in human and mouse tumor cell lines by MTT assays. In vivo anti-tumor potential was evaluated in Sarcoma-180 (S-180) and Ehrlich’s carcinoma (EC) solid tumors. Apoptosis in S-180 cells was analyzed by using Annexin V-Propidium Iodide (PI). Histological analysis of liver and kidney was performed at optimum dose (50 mg/kg). Expression status of CD4+, CD8+ and CD25+ cells in treated mouse were also examined. Results: Significant tumor growth retardation by the compounds was noted in early and advanced disease groups, as the life span of drug treated mice increased considerably. Drug induced killing was observed by induction of apoptosis. Naphthal-NU and 5-Nitro-naphthal-NU were effective to normalize the tumor induced structural abnormalities of liver and kidney. The compounds have no immunotoxic effect on CD4+ and CD8+ T cells and down regulate CD4+CD25+ regulatory T cells. Conclusion: Overall data holds promise for the antitumor activity with lower toxicity of the compounds that can be utilized for the treatment of human malignant tumors. Key Words: cytotoxicity, Naphthal-NU, Napro-NU, 5-Nitro-naphthal-NU, Sarcoma-180, Ehrlich’s carcinoma.